Preliminary Evaluation of Indigenous Ricebean Landraces under Red Lateritic Belt of West Bengal, India - Sarkar, N. C.; Ghosh, Biswajit; Maiti, Ratikanta; Thorie, Mhale; Rualthankhuma, C.; Teja K, Charan (International Journal of Bio-resource and Stress Management, 2023)
A field experiment on ricebean was conducted at the Agricultural Farm of the Institute of Agriculture (Palli Siksha Bhavana), Visva-Bharati, Sriniketan, West Bengal, India during July to December, 2013 to study the performance of few indigenous landraces collected from Nagaland and Mizoram states of India. The indigenous landraces collected are rhudi, rhuka, rhuwho-1, rhuwho-2, rhusie, rhujo, champhal, kolasib. They showed wide variability both in growth habit and yield attributes. Wide variability of test weight mainly differed the seed yield of the crop. The highest yield was recorded in rhusie cultivar (21 q ha-1) which was significantly higher than the all other cultivars like rhudi, rhuka, rhuwho-1, rhuwho-2, rhujo, champhal, kolasib. Though the rhusie cultivar test weight is low, but it recorded highest yield because of early onset of reproductive growth with more number of pickings. Rhuwho-2 cultivar recorded the second highest yield (19 q ha-1) which was significantly higher than the other cultivars like rhudi, rhuka, rhuwho-1, rhujo, champhal, kolasib. Lowest yield was recorded in rhuwho-1 cultivars (1 q ha-1).